COLONIZAÇÃO PELO ESTREPTOCOCO DO GRUPO B EM GESTANTES DURANTE O TRABALHO DE PARTO EM UMA MATERNIDADE DE SÃO LUÍS, MARANHÃO - Costa, Adriana Lima dos Reis (2008)
Objective: To study the colonization with group B streptococcus (GBS) in pregnant women near or in time for delivery. Methods: Vaginal and rectal cultures of 201 pregnant women were collected in the Marly Sarney Maternity in São Luís Maranhão, Brazil. The samples had been inoculated in Todd- Hewith selective media and then subcultured in plates of Agar-blood. The CAMP test was used for identification of the EGB. There were studied some demographic variables, obstetric antecedent and perinatal outcomes. The positive samples for EGB had been submitted to testing of sensitivity for antibiotics. Results: The prevalence of the maternal colonization with GBS was of 20.39%. There were not found association between the demographic variables and obstetric antecedents with higher presence of colonization with the EGB. There were two infectious outcomes between the newborns of colonized mothers however the hemocultures had been negative. Raised taxes of resistance for following antibiotics had been found: clindamicina 25.45%, eritromicina 23.63% and ceftriaxona 12.72%. Conclusion: The evidences point the presence of high taxes of maternal colonization with GBS that would indicate the systematic research of this agent among the pregnant women.